2011
DOI: 10.1016/j.envres.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions for asthma and acute bronchitis in El Paso, Texas: Do age, sex, and insurance status modify the effects of dust and low wind events?

Abstract: Background El Paso County (Texas) is prone to still air inversions and is one of the dust “hot spots” in North America. In this context, we examined the sub-lethal effects of airborne dust and low wind events on human respiratory health (i.e., asthma and acute bronchitis) between 2000 and 2003, when 110 dust and 157 low wind events occurred. Because environmental conditions may not affect everyone the same, we explored the effects of dust and low wind within three age groups (children, adults, and the elderly)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 53 publications
4
58
0
Order By: Relevance
“…Beyond increases in airborne particulate matter concentrations but short of the extreme of another Dust Bowl [ Lee and Gill , 2015; Sterk et al ., 2016], dust storms in the Southwest are known to be linked with numerous environmental impacts, including other respiratory diseases such as asthma and bronchitis [ Grineski et al ., 2011; Rodopoulou et al ., 2014], highway safety [ Hyers and Marcus , 1981], loss of efficiency of solar energy generation systems [ Sinha et al ., 2014], increased mountain snowmelt [ Skiles et al ., 2015; Clow et al ., 2016], changes to alpine ecosystems [ Steltzer et al ., 2009], loss of soil fertility/nutrients/carbon [ Alvarez et al ., 2012], and breakdown of soil structure [ Belnap and Gillette , 1998]. Thus, signs of an increase in dust storm activity also serve as warnings that numerous other environmental hazards will surely increase and act as a call for careful management and attention to these hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond increases in airborne particulate matter concentrations but short of the extreme of another Dust Bowl [ Lee and Gill , 2015; Sterk et al ., 2016], dust storms in the Southwest are known to be linked with numerous environmental impacts, including other respiratory diseases such as asthma and bronchitis [ Grineski et al ., 2011; Rodopoulou et al ., 2014], highway safety [ Hyers and Marcus , 1981], loss of efficiency of solar energy generation systems [ Sinha et al ., 2014], increased mountain snowmelt [ Skiles et al ., 2015; Clow et al ., 2016], changes to alpine ecosystems [ Steltzer et al ., 2009], loss of soil fertility/nutrients/carbon [ Alvarez et al ., 2012], and breakdown of soil structure [ Belnap and Gillette , 1998]. Thus, signs of an increase in dust storm activity also serve as warnings that numerous other environmental hazards will surely increase and act as a call for careful management and attention to these hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to dust particles has been associated with various detrimental effects on human health [e.g., Chen et al ., 2004; Perez et al ., 2008; Grineski et al ., 2011; Rodopoulou et al ., 2014]. The U.S. Centers for Disease Control and Prevention ( CDC ) [2013] reports a sharp increase of coccidioidomycosis incidences from 1998 to 2011 in the same regions where dust storms have increased.…”
Section: Dust Storms and Valley Fevermentioning
confidence: 99%
“…In Athens, Greece, Saharan dust events have been associated with a 2.54% increase of pediatric asthma hospital admissions based on a 10 µg/m 3 increase in PM 10 [79]. People of all ages in El Paso of Texas were 1.11 times more likely to be hospitalized by asthma on a dust event day than on a clear day [80]. Bell et al [81] investigated the relationship between cause-specific hospital admissions and sandstorms in Taipei, and that found asthma admissions rose 4.48% per 28 µg/m 3 increase in PM 10 levels.…”
Section: Desert Dust Associated With Asthma and Rhinitismentioning
confidence: 99%
“…23 In additions, a study showed that females were more sensitive to acute bronchitis after dust events than males. 24 Age is an independent factor associated with chronic bronchitis. A higher prevalence was observed in older people, 13 which is similar to our results (Table 4).…”
Section: Commentmentioning
confidence: 99%